The Effect of Online Loan Dependency on Students’ Investment Decisions: The Moderating Role of Financial Literacy, Consumptive Behavior, and Psychological Pressure - Resya Nabila; Lediana Sufina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The rapid development of financial technology (fintech) has contributed to the increasing use of online lending services among the public, including university students. The ease of access and fast approval processes have positioned online loans as an alternative source of financing. However, dependence on online lending may influence students’ financial conditions, consumption behavior, psychological stress, and investment decision-making. This study aims to examine the effect of online loan dependence on students’ investment decisions at STIE Indonesia Banking School, while considering financial literacy, consumptive behavior, and psychological stress as moderating variables. This research addresses a gap in prior studies, which have not sufficiently explained the relationship between online loan dependence and investment decisions by simultaneously integrating financial, behavioral, and psychological perspectives. A quantitative approach was employed using primary data collected through questionnaires distributed to 200 students who have experience using online lending services. The sampling technique used was purposive sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results show that financial literacy (β = 0.2128; p = 0.0274), consumptive behavior (β = 0.3881; p < 0.001), and psychological stress (β = 0.3026; p = 0.0004) have positive and significant effects on investment decisions. In contrast, online loan dependence does not significantly affect investment decisions (β = 0.0592; p = 0.2245). Moderation analysis indicates that consumptive behavior significantly moderates the relationship between online loan dependence and investment decisions (β = -0.2908; p = 0.0133), whereas financial literacy and psychological stress do not exhibit moderating effects. This study contributes to Behavioral Finance Theory by showing that investment decisions are shaped not only by financial factors but also by behavioral and psychological dimensions. The findings are expected to assist universities, regulators, and fintech providers in enhancing students’ financial literacy and promoting healthier financial behavior.